Subjectively and objectively assessed behavioral, social, and physical environmental correlates of sedentary behavior in preschoolers - Eichinger, Michael; Schneider, Sven; Bock, Freia de (The journal of pediatrics, 2018)
Objective - To investigate associations between preschoolers' objective leisure-time sedentary behavior and a comprehensive set of subjective and objective potential correlates of sedentary behavior across the behavioral, social, and physical environmental domains on both the family and community level. - Study design - In 3- to 6-year-old preschoolers (n = 738) from 52 preschools in Southern Germany, leisure time spent in sedentary behavior was assessed by accelerometry in 2008-2009. Family- and community-level potential correlates of sedentary behavior from different domains (behavioral, social, and physical environmental) were subjectively (ie, by parent-proxy report) and objectively (ie, by routine administrative data) assessed. - Results - None of the objective social and physical environmental correlates showed associations with sedentary behavior. Leisure-time sedentary behavior decreased with greater levels of moderate-to-vigorous physical activity (both weekends and weekday afternoons), participation in organized sports, parental leisure-time physical activity, as well as greater parental traffic safety perceptions (weekends only). - Conclusions - Targeting multiple health behaviors at the same time (ie, physical activity and sedentary behavior) and focusing on the entire family (ie, preschoolers, parents, and potentially older siblings) might be useful opportunities to reduce sedentary behaviors in preschoolers.
Gesehen am 05.08.2019